Revisiting the impact of families on family firm performance - Peter Jaskiewicz; James G. Combs; Klaus Uhlenbruck; Amlan Datta (European Management Review, 2023)
Family owners monitor managers, attenuating principal–agent conflicts and improving firm performance. However, family owners also appropriate resources, creating principal–principal conflicts that harm firm performance. Although these effects occur simultaneously, research does not explain when one outweighs the other. We theorize that agency costs are minimized when the family's involvement on the board of directors is proportional to its ownership; too little board involvement fuels principal–agent conflicts, and too much fuels principal–principal conflicts. Consistent with our theorizing, evidence from French panel data shows firm performance increases as family board involvement and family ownership jointly increase, and performance is maximized when family board involvement and family ownership are proportional.
Keywords: 650; agency theory; family board involvement; family business; family ownership; firm performance